The hard prison regime in Albania: an evaluation of its potential in countering organized crime and its ramifications = Strog zaporski režim v Albaniji : evalvacija njegovega potenciala v boju proti organizirani kriminaliteti in njenih posledic - Shala, Nita (Revija za kriminalistiko in kriminologijo, 2023)
In 2018, the Albanian legislature adopted the hard prison regime to respond to organized crime. The regime consists of a temporary suspension of detention protocols for persons in custody believed to be connected with organized criminal groups, based on an order from the Minister of Justice. Through face-to-face interviews with prosecutors, judges, defense attorneys, government officials, civil society representatives, and academics, this study examines the essential characteristics of the regime, its legal basis, its effectiveness in achieving the desired result, and the undesired consequences. The findings reveal diverse perspectives on the regime’s effectiveness, with some interviewees acknowledging its potential to sever ties between leaders and criminal organizations. In contrast, others question its limited scope and potential human rights violations. This paper offers insights to inform future legal reforms and policies, emphasizing the need for a balanced approach that upholds human rights while tackling organized crime effectively.